Perencanaan Kawasan Pesisir Berbasis Ekowisata Dan Minapolitan di Desa Lamreh, Kecamatan Mesjid Raya, Kabupaten Aceh Besar - Agussaini, Halis Agussaini; Rizkiya, Putra; Gunawan, Arief (Yayasan Kawanad, 2024)
Community engagement towards the Lamreh community aims to strengthen sustainable development in coastal areas. This activity aims to Through a participatory approach, the lecturers collaborate with the Lamreh community and relevant stakeholders to identify the potential and challenges in the development of ecotourism and minapolitan. The engagement is conducted through field surveys, interviews, and group discussions. The results indicate that Lamreh has great natural potential, especially in the fisheries and tourism sectors, which can be developed sustainably. In an effort to improve coastal area management, several strategies are proposed, including the development of environmentally friendly tourism infrastructure, promotion of local products, increasing community capacity in marketing and management, as well as marine environmental protection and preservation. This community engagement provides a positive contribution to empowering the local community, enhancing their participation in local development, and creating sustainable development models that can be adopted in other coastal areas. In conclusion, collaboration between academics, government, and communities is crucial in planning and implementing sustainable development programs in coastal areas such as Lamreh Village, Aceh Besar Regency.